Police Warriors and Police Guardians: Race, Masculinity, and the Construction of Gun Violence. (8th August 2019) - Carlson, Jennifer
Abstract: This paper draws on 79 in-depth interviews with police chiefs in Arizona, California, and Michigan to advance sociological understandings of race, masculinity, and policing. While the bulk of scholarship on public law enforcement focuses on urban settings, this paper juxtaposes police's perceptions of urban, suburban, and rural gun violence. It details how police chiefs construct criminal gun violence according to two overarching tropes: (1) gang- and drug-related gun violence involving black and brown perpetrators and victims in urban spaces and (2) active shooting-related gun violence involving white perpetrators and victims in suburban and rural spaces. The analysis shows that police understand their own guns in part through reference to these tropes, embracing two racially distinct styles of police masculinity: the "warrior" and the "guardian." Whereas the "warrior" brand of police masculinity emphasizes aggressive enforcement against (black and brown) perpetrators, the "guardian" brand of police masculinity emphasizes assertive protection on behalf of (white) victims. Detailing masculinity as a bifurcated axis along which racialized policing is enacted and amplified, this study broadens scholarly understandings of public law enforcement as a race-making institution and suggests the limitations of police reforms that fail to address whiteness as shaping public law enforcement.